Military computer games and the new American militarism: what computer games teach us about war - Thomson, Matthew Ian Malcolm (2009)
Military computer games continue to evoke a uniquely contradictory public, intellectual, and critical response. Whilst denigrated as child’s play, they are played by millions of adults; whilst dismissed as simplistic, they are used in education, therapy, and military training; and whilst classed as meaningless, they arouse fears over media effects and the propagandist influence of their representations of combat. They remain the object of intense suspicion, and as part of a new and growing mass medium, they are blamed for everything from obesity to falling literacy standards, and from murder to Abu Ghraib. Much of the suspicion surrounding military computer games has been caused by the development of the military-entertainment complex - the relationship between the computer game industry and the U.S. military which has seen the production of dual-use games, co-produced by the military and the computer game industry and released for both military training and commercial sale. This relationship has placed military computer games at the centre of an intensely politicized debate in which they have become characterized as a mass medium which functions under the control of the military and political establishment and which promotes the militaristic ideals of the neoconservative Bush administration. This thesis serves as a fundamental reevaluation of such preconceptions and prejudices, and in particular, a complete reevaluation of the understanding of the relationship between computer games and American militarism. Its analysis focuses on three main areas: firstly, the content of military computer games; secondly, the determinants which affect the production and representation of war in computer games; and thirdly, the contribution of the representation of war in computer games to the misunderstandings and misconceptions concerning warfare which, in turn, have supported American militaristic beliefs.